2013
DOI: 10.1007/s10620-013-2850-3
|View full text |Cite
|
Sign up to set email alerts
|

Dyssynergic Defecation: A Treatable Cause of Persistent Symptoms When Inflammatory Bowel Disease Is in Remission

Abstract: Despite remission, some inflammatory bowel disease patients have persistent defecatory symptoms. Defecatory symptoms may not be predictive of an underlying inflammatory disorder. Lack of inflammatory activity and absence of left-sided disease should prompt investigation of functional disorders. Anorectal manometric testing and biofeedback therapy for patients with a diagnosis of dyssynergia may be a useful therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 16 publications
0
38
0
Order By: Relevance
“…82 Biofeedback therapy in this cohort has demonstrated encouraging results with up to 80% of patients reporting improvement in symptoms. 82 Biofeedback has also been utilised with success in patients with multiple sclerosis, spinal cord and neurogenic bowel dysfunction. 83,84 In addition, for practical purposes, home biofeedback may enable patients in rural or regional settings to access treatment using an EMG home trainer or silicone probe device and has demonstrated encouraging results.…”
Section: Furth Er Areas Of Interestmentioning
confidence: 75%
See 1 more Smart Citation
“…82 Biofeedback therapy in this cohort has demonstrated encouraging results with up to 80% of patients reporting improvement in symptoms. 82 Biofeedback has also been utilised with success in patients with multiple sclerosis, spinal cord and neurogenic bowel dysfunction. 83,84 In addition, for practical purposes, home biofeedback may enable patients in rural or regional settings to access treatment using an EMG home trainer or silicone probe device and has demonstrated encouraging results.…”
Section: Furth Er Areas Of Interestmentioning
confidence: 75%
“…It has been found that a significant number of patients with inflammatory bowel disease who have evacuatory dysfunction may also have concomitant pelvic floor dyssynergia . Biofeedback therapy in this cohort has demonstrated encouraging results with up to 80% of patients reporting improvement in symptoms . Biofeedback has also been utilised with success in patients with multiple sclerosis, spinal cord and neurogenic bowel dysfunction .…”
Section: Further Areas Of Interestmentioning
confidence: 95%
“…4 Exploration of IBS symptoms may include testing to rule out pelvic floor disorders with anorectal manometry and balloon expulsion test in those with chronic constipation, fecal incontinence, overflow diarrhea, or other defecatory disorders, as these conditions may respond to biofeedback therapy. 46 Psychiatric or psychological disturbances are associated with IBS-like symptoms in IBD while anxiety and reduced vitality have been shown to independently predict IBS-like symptoms. 13 All aforementioned noninflammatory perturbations, together with potential investigative approaches, are outlined in the Table 1.…”
Section: Functional Gi Symptoms In Ibdmentioning
confidence: 99%
“…The application of pelvic floor therapy targeting dyssynergic defecation has shown gratifying benefit in many patients with IBS and constipation. In a study of 30 patients with IBD in remission and defecatory disorders, 30% had clinically relevant benefit from biofeedback therapy 46 The potential for such an approach in those with functional symptoms requires greater exploration.…”
Section: Pelvic Floor Therapymentioning
confidence: 99%
“…In a cohort of 177 patients with inflammatory bowel disease (IBD) referred for anorectal testing, 46% of patients had a DD; the prevalence of a DD was higher in patients with Crohn’s disease than ulcerative colitis [7]. In another study, 29 of 30 patients with inflammatory bowel disease and persistent lower GI symptoms without left colonic inflammation had a DD [8]•. Moreover, symptoms improved in 30% of these patients following pelvic floor biofeedback therapy.…”
Section: Defecatory Disordersmentioning
confidence: 99%